IDE-IDE FEMINIS SEBAGAI RESISTENSI TERHADAP KETIDAKADILAN GENDER KAJIAN KRITIK FEMINIS TERHADAP FILM âA HOT ROOFâ - , SRI AYU NINGSIH; , Yuni Wachid Asrori, S.S., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In the early 1990, Korean society has lost the power to do demonstrations . Many of the intellectuals demonstrators broke away from the field and the organization . Attention to political and social replaced by a problem in the field of culture . One concern to fill the void is a problem concerning women's issues . Because of this phenomenon, in the early 1990 many emerging a wide variety of films dealing with issues concerning women's issues . In spite of various limitations, the independence of women's issues had been directed as outlined in the plot of the movie . But after the mid 1990, the traces of this trend was concealed. Then the various issues of womenâs concern appeared with a different matter. The representative one was titled ê° ê°ì ë  ì ì¤í ( A Hot Roof ). This movie described about the unity of strong women in fighting against gender inequality in violence era. The women criticized the potential of violence structure and collective violence committed by men in one voice. To find the feminist ideas in this movie, the authors analyze the dialogue and divide the actorâs character into Profeminism and Contrafeminism. Profeminism actor is a figure who oppose the gender injustice. The actors are Jeong Hee, Kyeong Seok, Yeong Heeâs mother, Eunjuâs mother, Kongjuâs mother, dan Yoon Hee. Profeminism actor is a figure that supports of patriarchy system. The actors are Ki Soon, Seong Goo, Yeong Heeâs father and police captain. This movie reveals many of the limitations of gender to women such as domestic violence, subordination of women which limit the space for women in the outside, and negative stereotypes like women only obliged to serve her husband, caring for their child, managing the household, women that live without a husband (widow) and all women who work as a hostess considered as a bad women. The feminist ideas of A Hot Roof movie is the courage of women who can choose their own path and social transformation effort. This movie also tell us about womanâs imaging as a seductive women even if a women is weak creature that can be exploited by men. The strong female characters who dare to resist domination and to express their desire inspire all women to fight for gender equality between women and men